Exploring Metadiscourse Use in Thesis Abstracts: A Cross-Cultural Study - Ardi Nugroho (Universitas Bunda Mulia, 2019)
The use of metadiscourse in academic writing has become a topic of interest in recent years. It can be defined as the words and phrases that writers use in their writing to express their ideas and thoughts to make it easier for readers to process the information presented. It is especially crucial in academic writing since writers are expected to present their arguments in an appropriate and acceptable manner. It has also been said that culture plays a role influencing how arguments and ideas are expressed, especially in academic writing. Although metadiscourse plays an integral role in academic writing, studies have shown how EFL learners often make mistakes in employing this linguistic device. From this, the writer would like to explore the metadiscourse produced by Indonesian EFL learners and compare it with how native speakers of English employ metadiscourse in their writing. In other words, this study is basically an attempt to find out whether the metadiscourse produced by the two groups with different cultural backgrounds are different or similar. The source of data for the current study is the metadiscourse markers from the thesis abstracts of students of the English Language and Culture Department at Bunda Mulia University and American students from a university in the U.S. In order to analyze the metadiscourse markers found in the thesis abstracts of the Indonesian and American students, the writer will make use of the AntConc software version 3.5.6 by Anthony (2018). The result of the study reveals that there are some differences and similarities in the way both group of students employed these markers.Keywords: metadiscourse, thesis abstracts, Indonesian and American students